Assistance of â€œAisyiyahâ€ Women Crisis Center to Children of Incest Victims - Tursilarini, Tateki Yoga (Jurnal Penelitian Kesejahteraan Sosial, 2018)
Bodies and institutions that handle sexual violence cases, particularly incest case, still need more holistic effort in doing so by involving various bodies or institutions of children care. This study is aimed to describe the process of handling incest violence and the form of assistance for victims of incest violence. Data sources are WCC staffs, volunteers/companions, victims and victim’s parents, Trauma Center Protection Home (Rumah Perlindungan Trauma Center = RPTC). Techniques of data collecting were carried out through interview and observation, descriptive qualitative data analysis on such cases and through interventions conducted by WCC Aisyiyah to the victims. The research’s findings showed that there were some stages of service process as follows: Doing initial introduction; Making contact to the victims and providing contract of handling; Assessing the victims; Undertaking an intervention plan; Implementing the intervention stages; Conducting evaluation and termination. Forms of assistance undertaken by WCC Aisyiyah include these followings: legal consultations; referring to a psychologist; litigation assistance / legal assistance; approach to victims and assistance for victims; referring victims to come to the assigned shelters for trauma healing; reporting to the legal side; motivating victims; social assistance according to the needs of victims; referring the victims to attend the shelter of Social Bodies (Dinas Sosial) or RPTC to get the psychological services, religious advices, and health service; providing UEP assistance for victims for the sake of their survival effort; offering assistance in undergoing the authority’s investigation (BAP), or that of visum et repertum and trial process. This research recommends several points as follows: 1) the need of top-down socialization activities on Child Protection Act No. 23/2002 to the lowest level of society’s authorities (RT / RW), to families, to schools and religious leaders and to community. 2) preferences of taking side for legal authorities to violence victim children, 3) the need of assistance for victims by the time of reporting the case to the police/authorities, so that children’s rights are protected as the victims of sexual violence/ incest. 4) the need of increasing the involvement of related foundation or social institutions to provide any necessary possible solution for the sexual violence/ incest victims children.